2019
DOI: 10.1002/aorn.12583
|View full text |Cite
|
Sign up to set email alerts
|

OR Time and Sacral Pressure Injuries in Critically Ill Surgical Patients

Abstract: Critically ill patients are at risk for developing pressure injuries during operative and other invasive procedures. The purpose of this secondary analysis was to explore the relationship of OR time to sacral pressure injuries in critically ill patients using high frequency ultrasound as a method of assessment. The 41 participants examined in this study had both time in the OR and up to eight days of pressure injury data. The multivariable model containing OR bed time, body mass index, and Braden Scale score p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…All perioperative patients are at risk for pressure injury because they are immobile during the procedure; unable to feel pain caused by pressure, friction, or shear forces; and unable to change position to relieve the pressure on a particular area . Studies correlating the length of the operative or other invasive procedure and pressure injury development are inconclusive . A recent study focusing on sacral pressure injuries in critically ill surgical patients found that a shorter procedure duration increased the risk of pressure injuries .…”
Section: Surgical Patients and Pressure Injuriesmentioning
confidence: 99%
See 2 more Smart Citations
“…All perioperative patients are at risk for pressure injury because they are immobile during the procedure; unable to feel pain caused by pressure, friction, or shear forces; and unable to change position to relieve the pressure on a particular area . Studies correlating the length of the operative or other invasive procedure and pressure injury development are inconclusive . A recent study focusing on sacral pressure injuries in critically ill surgical patients found that a shorter procedure duration increased the risk of pressure injuries .…”
Section: Surgical Patients and Pressure Injuriesmentioning
confidence: 99%
“…15,16 Studies correlating the length of the operative or other invasive procedure and pressure injury development are inconclusive. [17][18][19] A recent study focusing on sacral pressure injuries in critically ill surgical patients found that a shorter procedure duration increased the risk of pressure injuries. 17 However, other studies report that the risk of pressure injury increases up to 48% for every hour after the initial 60 minutes of a procedure.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research exploring factors associated with postoperative pressure injury development is greatly appreciated as a means of examining our practice and the interventions designed to prevent adverse clinical outcomes. Although this study adds to the current knowledge regarding the association of body mass index and Braden score to postoperative pressure injury risk, a key takeaway was that longer OR time and OR bed time were associated with a decreased risk for postoperative pressure injury in the critically ill surgical patient . These findings are perplexing and dispute the current body of evidence .…”
mentioning
confidence: 74%
“…From a statistical viewpoint, we question the validity of the reported results given the small sample size and stepwise modeling procedure. Although we appreciate the authors’ stated desire to “not include more variables than the sample size allowed,” (p232) the performed logistic regression including three variables for 51 total cases and 16 positive cases does not meet general statistical guidelines. Conventional recommendations suggest always including a minimum of 100 total cases and obtaining at least 10 cases (of each outcome) for every candidate variable in the modeling scenario .…”
mentioning
confidence: 99%